The European corn borer, Ostrinia nubilalis [Lepidoptera : Pyralidae] : a potential pest of potatoes growth on Prince Edward Island - Stewart, J.G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
The effects of the European corn borer, Ostrinia nubilalis [Lepidoptera: Pyralidae], on yield of 'Russet Burbank' potatoes (Solanum tuberosum) was investigated at two sites in Prince-Edward-Island in 1989 and 1990. At Summerside, the mean number of larvae per stalk did not exceed 0.19 in either year, and no significant differences in yield were found between untreated plots (check) and plots protected with Bacillus thuringiensis var. kurstaki (B.t.k.). At Tryon in 1989, a seasonal average of 1.16 larvae per stalk reduced total and marketable yields by 7.5% and 8.8%, respectively, compared to plots protected with B.t.k. A similar but not statistically significant trend was observed in 1990 at this site. The higher degree of damage by the European corn borer to potatoes grown on P.E.I., relative to crops grown in more southernly locations, may be due to the longer interval of attack. On P.E.I., the action threshold for the European corn borer on potatoes appears to be between 0.11 and 0.30 egg masses per stalk.